A Focus on the Cerebellum: From Embryogenesis to an Age-Related Clinical Perspective - Amore, Greta; Spoto, Giulia; Ieni, Antonio; Vetri, Luigi; Quatrosi, Giuseppe; Di Rosa, Gabriella; Nicotera, Antonio Gennaro (Frontiers in Systems Neuroscience, 2021)
The cerebellum and its functional multiplicity and heterogeneity have been objects of curiosity and interest since ancient times, giving rise to the urge to reveal its complexity. Since the first hypothesis of cerebellar mere role in motor tuning and coordination, much more has been continuously discovered about the cerebellum's circuitry and functioning throughout centuries, leading to the currently accepted knowledge of its prominent involvement in cognitive, social, and behavioral areas. Particularly in childhood, the cerebellum may subserve several age-dependent functions, which might be compromised in several CNS pathologies. Overall, cerebellar damage may produce numerous signs and symptoms and determine a wide variety of neuropsychiatric impairments already during the evolutive age. Therefore, an early assessment in children would be desirable to address a prompt diagnosis and a proper intervention since the first months of life. Here we provide an overview of the cerebellum, retracing its morphology, histogenesis, and physiological functions, and finally outlining its involvement in typical and atypical development and the age-dependent patterns of cerebellar dysfunctions.